KAJIAN ADOPSI INOVASI POLA TANAM JAJAR LEGOWO PADA USAHATANI PADI SAWAH - Ade Fijar Septiana; Pujiharto Pujiharto; Sulistyani Budiningsih (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2016)
This research was conducted in Pabuaran village, Salem Sub-district, Brebes regency. This research aims were to describe adoption level and factor sthat affected farmer’s adoption system of pair rowson Sekar Arum farmers using method of descriptive case study. The dataof this research were primary and secondary data. The technique of sampling used census technique that was the members of Sekar Arum farmers that contained 35 farmers.The result of this research concludes that theage of respondents are in productive age with loweducation level. Most of the farmers are in low education level and owns narrow rice field that is less than 0,5 ha. The result of descriptive quantitative analysis through Likert scoring showed that the adoption level of pair rowson rice farming that is categoraed in high level is17,l % or 6 farmers, in medium category is 80% or 28 farmers and in low category is 2,9% or a farmer. The result of logistic analysis through SPSS for Windows Realese 22,00 on signifacance level of SYo shows that the level of education variable significantly affectstowards the adoption level of pair rows cultivation system. Yet, the other variebles do not significantly affect as the significance level is bigger than the real significance that is 0,05.